The Emerging Role of Plant-Derived Exosomes-Like Nanoparticles in Immune Regulation and Periodontitis Treatment - Zhang, Zeyu; Yu, Yang; Zhu, Guanxiong; Zeng, Liting; Xu, Shaofen; Cheng, Haoyu; Ouyang, Zhaoguang; Chen, Jianwei; Pathak, Janak L.; Wu, Lihong; Yu, Lina (Frontiers in Immunology, 2022)
Periodontitis is an infectious oral disease, which leads to the destruction of periodontal tissues and tooth loss. Although the treatment of periodontitis has improved recently, the effective treatment of periodontitis and the periodontitis-affected periodontal tissues is still a challenge. Therefore, it is urgent to explore new therapeutic strategies for periodontitis. Natural products show anti-microbial, anti-inflammatory, anti-oxidant and bone protective effects to periodontitis and most of these natural products are safe and cost-effective. Among these, the plant-derived exosome-like nanoparticles (PELNs), a type of natural nanocarriers repleted with lipids, proteins, RNAs, and other active molecules, show the ability to enter mammalian cells and regulate cellular activities. Reports from the literature indicate the great potential of PELNs in the regulation of immune functions, inflammation, microbiome, and tissue regeneration. Moreover, PELNs can also be used as a drug carrier to enhance drug stability and cellular uptake in vivo. Since regulation of immune function, inflammation, microbiome, and tissue regeneration are the key phenomena usually targeted during periodontitis treatment, the PELNs hold the promising potentials of periodontitis treatment. This review summarizes the recent advances in PELNs-related research that are related to the treatment of periodontitis and regeneration of periodontitis-destructed tissues and the underlying mechanisms. We also discuss the existing challenges and prospects of the application of PELNs-based therapeutic approaches for periodontitis treatment.